Patterns and correlates of illicit drug selling among youth in the USA - Ahmedani B; Abdon A; Perron BE; Shook JJ; Vaughn MG (Dove Medical Press, 2011)
Michael G Vaughn1, Jeffrey J Shook2, Brian E Perron3, Arnelyn Abdon4, Brian Ahmedani51School of Social Work, School of Public Health and Department of Public Policy Studies, Saint Louis University, St Louis, MO USA; 2School of Social Work, University of Pittsburgh, Pittsburgh, PA USA; 3School of Social Work, University of Michigan, Ann Arbor, MI USA; 4School of Economics, University of the Philippines, Quezon City, Philippines; 5Henry Ford Health System, Detroit MI, USAPurpose: Despite the high rates of drug selling among youth in juvenile justice and youth residing in disadvantage neighborhoods, relatively little is known about the patterns of illicit drug selling among youth in the general population.Methods: Using the public-use data file from the adolescent sample (N = 17 842) in the 2008 National Survey on Drug Use and Health (NSDUH), this study employed multiple logistic regression to compare the behavioral, parental involvement, and prevention experiences of youth who sold and did not sell illicit drugs in the past year.Results: Findings from a series of logistic regression models indicated youth who sold drugs were far more likely to use a wide variety of drugs and engage in delinquent acts. Drug-selling youth were significantly less likely to report having a parent involved in their life and have someone to talk to about serious problems but were more likely to report exposure to drug prevention programming.Conclusion: Selling of drugs by youth appears to be a byproduct of substance abuse and deviance proneness, and the prevention programs these youth experience are likely a result of mandated exposure derived from contact with the criminal justice system. Assuming no major drug supply side reductions, policies, and practices associated with increasing drug abuse treatment, parental involvement and supervision, and school engagement are suggested.Keywords: drug distribution, prevention, adolescent risk, youth experiences, parental involvement